2022
DOI: 10.1002/slct.202203763
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Quinoline‐Morpholine‐Coupled 1,2,3‐Triazole Hybrids as In vitro EGFR inhibitors

Abstract: Herein we described the synthesis of some new quinolinemorpholine coupled 1,2,3-triazole hybrids (6 a-n) from 5chloroquinolin-8-ol using well known reactions like Mannich reaction, O-propargylation, and finally copper (I) catalyzed azide-alkyne cycloaddition (CuAAC). The structures of all newly synthesized hybrids were confirmed by 1 H-NMR, 13 C-NMR, and Mass spectra. All of them were screened for their in vitro cytotoxicity towards three human cancer cell lines including MCF-7, A549 and HepG2 by MTT assay whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 44 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…1,2,3-Triazole-quinoline hybrids 84 (IC 50 : 1.10-60.56 µM, MTT assay) exhibited moderate to excellent antiproliferative activity against MCF-7 breast cancer cells, and the SAR indicated that the methoxy group on the phenyl ring at N-1 position of 1,2,3-triazole motif could increase the activity. [110] In particular, hybrids 84a-c (2) halogen atom at R position was favorable to the activity. [111] The 1.28 and 7.34 µM) against MCF-7 and MDA-MB-231 breast cancer cell lines.…”
Section: Indole-pyridine/quinoline Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2,3-Triazole-quinoline hybrids 84 (IC 50 : 1.10-60.56 µM, MTT assay) exhibited moderate to excellent antiproliferative activity against MCF-7 breast cancer cells, and the SAR indicated that the methoxy group on the phenyl ring at N-1 position of 1,2,3-triazole motif could increase the activity. [110] In particular, hybrids 84a-c (2) halogen atom at R position was favorable to the activity. [111] The 1.28 and 7.34 µM) against MCF-7 and MDA-MB-231 breast cancer cell lines.…”
Section: Indole-pyridine/quinoline Hybridsmentioning
confidence: 99%
“…1,2,3‐Triazole‐quinoline hybrids 84 (IC 50 : 1.10–60.56 µM, MTT assay) exhibited moderate to excellent antiproliferative activity against MCF‐7 breast cancer cells, and the SAR indicated that the methoxy group on the phenyl ring at N‐1 position of 1,2,3‐triazole motif could increase the activity. [ 110 ] In particular, hybrids 84a–c (IC 50 : 1.10, 3.88, and 3.10 µM, respectively) not only were more potent than erlotinib (IC 50 : 4.15 µM) against MCF‐7 breast cancer cells but also displayed low cytotoxicity (IC 50 : 95.05, 91.14 and 89.26 µM, respectively) toward normal MCF‐10A breast cells. Moreover, the most active hybrid 84a (IC 50 : 140 nM) was also more potent than erlotinib (IC 50 : 420 nM) in terms of inhibition of EGFR.…”
Section: Indole‐pyridine/quinoline Hybridsmentioning
confidence: 99%
“…cell lines using the MTT assay. [31][32][33] Here, erlotinib was used as a positive control, and the results were presented in IC 50 with μM. From the obtained cytotoxicity results (Table 2), it is obvious that the compounds showed varied levels of cytotoxic activity against tested cancer cell lines, ranging from strong, good, moderate, and weak.…”
Section: In Vitro Cytotoxicitymentioning
confidence: 99%
“…Newly synthesized fully decorated sulfonyl 1,2,3‐triazoles ( 5 a – 5 g and 6 a – 6 g ) were then investigated for their in vitro cytotoxicity against MCF‐7 (ATCC‐HTB‐22), MDA‐MB‐231 (ATCC‐HTB‐26), A‐549 (ATCC‐CCL‐185), and MCF‐10 A (ATCC‐CRL‐10317). cell lines using the MTT assay [31–33] . Here, erlotinib was used as a positive control, and the results were presented in IC 50 with μ M. From the obtained cytotoxicity results (Table 2), it is obvious that the compounds showed varied levels of cytotoxic activity against tested cancer cell lines, ranging from strong, good, moderate, and weak.…”
Section: Chemistrymentioning
confidence: 99%
“…In continuation of our work to synthesize biologically active hybrids, [24][25][26][27] here we have designed (Figure 2) the compounds that consists of two pharmacophores (quinoline and isoxazole) by taking in to consideration of the above stated biological applications of isoxazole and quinoline and advantages of the pharmacophore hybridization. [28,29] Results and Discussion Chemistry Synthesis of the target compounds (5 a-5 n) was achieved in three steps as shown in Scheme 1.…”
Section: Introductionmentioning
confidence: 99%